Moral distress and burnout in Iranian nurses: The mediating effect of workplace bullying - Ajoudani, Fardin (Nursing ethics, 2019)
Background:Moral distress and workplace bullying are important issues in the nursing workplace that appear to affect nurse’s burnout.Aim:To investigate the relationship between moral distress and burnout in Iranian nurses, as mediated by their perceptions of workplace bullying.Ethical considerations:The research was approved by the committee of ethics in research of the Urmia University of Medical Sciences.Method:This is a correlation study using a cross-sectional design with anonymous questionnaires as study instruments (i.e. Moral Distress Scale-Revised, Maslach Burnout Inventory and The Negative Acts Questionnaire-Revised). Data were collected from 278 nurses from five teaching hospitals in Urmia, the capital of Western Azerbaijan, northwest of Iran. Structural equation modeling and bootstrapping procedures were employed to recognize the mediating role of their perceptions of workplace bullying.Results:The mean score of moral distress, burnout, and the Negative Acts Questionnaire-Revised Scale among the participants were 91.02 ± 35.26, 79.9 ± 18.27, and 45.4 ± 15.39, respectively. The results confirmed our hypothesized model. All the latent variables of study were significantly correlated in the predicted directions. The moral distress and bullying were significant predictors of burnout. Perception of bullying partially mediated the relationship between moral distress and burnout. The mediating role of the bullying suggests that moral distress increases burnout, directly and indirectly.Conclusion:Nursing administrators should be conscious of the role of moral distress and bullying in the nursing workplace in increasing burnout.